United Kingdom : Financial Sector Assessment Program-The Bank of England's Stress Testing Framework-Technical Note. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses the Bank of England's (BoE's) stress testing program, including both the concurrent stress test and the stress testing done by the banks through the Internal Capital Adequacy Assessment Process, though with a clear focus on the former. The stress test is meant to generate information on potential vulnerabilities of the system to emerging and growing risks, both financial and in the real economy. The main purpose of the stress testing framework is to provide a forward-looking, quantitative assessment of capital adequacy of the U.K. banking system as a whole, and individual institutions within it. The stress-testing program is evaluated along five dimensions: scope of coverage, scenario design, analytical infrastructure, disclosure, and governance.